Clinical effect and safety profile of recombinant human lysosomal acid lipase in patients With cholesteryl ester storage disease. Issue 3 (28th March 2013) - Balwani, Manisha; Breen, Catherine; Enns, Gregory M.; Deegan, Patrick B.; Honzík, Tomas; Jones, Simon; Kane, John P.; Malinova, Vera; Sharma, Reena; Stock, Eveline O.; Valayannopoulos, Vassili; Wraith, J. Edmond; et al.
<x xml:space="preserve">Abstract</x> Cholesteryl ester storage disease (CESD), an inherited deficiency of lysosomal acid lipase (LAL), is an underappreciated cause of progressive liver disease with no approved therapy. Presenting features include dyslipidemia, elevated transaminases, and hepatomegaly. To assess the clinical effects and safety of the recombinant human LAL, sebelipase alfa, nine patients received four once‐weekly infusions (0.35, 1, or 3 mg·kg−1) in LAL‐CL01, which is the first human study of this investigational agent. Patients completing LAL‐CL01 were eligible to enroll in the extension study (LAL‐CL04) in which they again received four once‐weekly infusions of sebelipase alfa (0.35, 1, or 3 mg·kg−1) before transitioning to long‐term every‐other‐week infusions (1 or 3 mg·kg−1). Sebelipase alfa was well tolerated, with mostly mild adverse events unrelated to sebelipase alfa. No antidrug antibodies were detected. Transaminases decreased in patients in LAL‐CL01 and increased between studies. In seven patients receiving ongoing sebelipase alfa treatment in LAL‐CL04, the mean ± standard deviation (SD) decreases for alanine transaminase and aspartate aminotransferase at week 12 compared to the baseline values in LAL‐CL01 were 46 ± 21 U/L (−52%) and 21 ± 14 U/L (−36%), respectively (P ≤ 0.05). Through week 12 of LAL‐CL04, these seven patients also showed mean decreases from baseline in total cholesterol of 44 ± 41 mg/dL (−22%; P = 0.047), low density lipoprotein‐cholesterol of 29 ± 31 mg/dL (−27%; P = 0.078), and triglycerides of 50 ± 38 mg/dL (−28%, P = 0.016) and increases in high density lipoprotein‐cholesterol of 5 mg/dL (15%; P = 0.016). Conclusion: These data establish that sebelipase alfa, an investigational enzyme replacement, in patients with CESD is well tolerated, rapidly decreases serum transaminases, and that these improvements are sustained with long‐term dosing and are accompanied by improvements in serum lipid profile. (HEPATOLOGY 2013;58:950–957)